Relocalización y diseño arquitectonico del Hospital Municipal De Acacias-Meta. (2020)
This work summarizes the study and process of architecture as a profession. It is about the city and each of the elements that it consists of. Architects have the function of planning, integration and organization in each of the essential relationships concerning the population. All of these elements are considered within the Town and Country Planning Department (POT) which is the entity in change of planning and order of the state. It establishes each of the appropriate uses in the different activities for the structuring of the context of the city. That is how it determines the equipment for the basic needs of inhabitants; such as: institutional, education, health-care, cultural, religious and sports among others. Health-care makes part of one of the most important organizations of the city for its institutions and equipment. Thus, an analysis of the Colombian territory is carried out in the context of the nation. Our focus is the municipality of Acacias, which belongs to Meta state. The rural, urban and contextual component of the municipality is studied. Hence, it determines that health- care services have coverage in villages, municipalities and regional influence but it consolidates within the urban area. At the same time, the present project is defined to respond to each of the identified problems, among them the relocation of the new municipal hospital which has the goal of taking care of coverage and population demand concerning the provision of health-care services of the third level.